P2.085 The Current Antimicrobial Susceptibility in Chlamydia Trachomatis in Japan from the Nationwide Surveillance. (13th July 2013) - Takahashi, S; Matsumoto, T; Yamamoto, S; Ishikawa, K; Uehara, S; Hamasuna, R; Yasuda, M; Hayami, H; Hanaki, H; Kadota, J
Abstract : Chlamydia trachomatis is one of the principal pathogens for non-gonococcal urethritis. There have been a few studies about novel resistant strains isolated from the patients with genital chlamydial infection. However, the current common concept indicates that those were temporary and unstable strains with decreased antimicrobial susceptibility. Three societies, the Japanese Society of Chemotherapy, Japanese Association of Infectious Diseases and Japanese Society of Clinical Microbiology, performed the first national surveillance for C. trachomatis between April 2009 and October 2010. Based on the data obtained, the current situation of antimicrobial susceptibility in C. trachomatis and the results of the previous research on antimicrobial susceptibility in M. genitalium are discussed. In 51 medical facilities in 8 prefectures of Japan, urethral discharge or urethral swab specimens were collected from male patients with urethritis. The specimens were sent to the Kitazato University Research Center for Anti-infectious Drugs via BD Universal Viral Transport. There, measurement of antimicrobial susceptibilities was performed according to the standard method of the Japan Society of Chemotherapy. The drugs used for antimicrobial susceptibility testing are shown below. From 28 facilities, 207 specimens were collected and 48 specimens were positive for C. trachomatis by culture. Using these specimens, antimicrobial susceptibility testing could be performed for 19 strains. The MIC50, MIC90 and range (μg/ml) were as follows. EM: 0.06, 0.25, and 0.03∼0.25: CAM: 0.008, 0.016, and 0.004∼0.03; AZM: 0.125, 0.5, and 0.06∼0.5; MINO: 0.5, 1, and 0.125∼2; DOXY: 0.125, 0.25, and 0.03∼0.5 μg/ml; CPFX: 2, 4, and 1∼4; LVFX: 0.25, 0.25, and 0.125∼0.5; TFLX: 0.125, 0.25, and 0.06∼0.5; STFX: 0.06, 0.125, and 0.03∼0.25. Fortunately, there were no resistant strains of C. trachomatis in this surveillance. However, the current and future situation of antimicrobial susceptibility in the pathogens of non-gonococcal urethritis will be surveyed regularly.